1971
DOI: 10.1111/j.1476-5381.1971.tb07137.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α‐methyl‐p‐tyrosine, p‐chlorophenylalanine, l‐β‐(3,4‐dihydroxyphenyl)alanine, 5‐hydroxytryptophan and diethyldithiocarbamate on the analgesic activity of morphine and methylamphetamine in the mouse

Abstract: Summary1. The analgesic activity of sympathomimetic drugs does not appear to involve a peripheral component. 2. Drugs causing changes in morphine analgesia have similar effects on the analgesia produced by methylamphetamine. 3. The analgesia produced by morphine and methylamphetamine is increased by drugs which increase the ratio of brain 5-hydroxytryptamine (5-HT) to dopamine. 4. The analgesia is decreased by drugs causing a fall in brain 5-HT or a rise in dopamine relative to 5-HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(19 citation statements)
references
References 18 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…The timedependent effect rules out the possibility that AMPT acted proactively on processes directly associated with the test of analgesia. This is of importance because Major and Pleuvry (1971) demonstrated that AMPT potentiates the analgesic effects of morphine even though less extensive studies by Fenessy and Lee (1970) and Verri et al (1968) showed either no effect or an antagonistic effect upon morphine-induced analgesia. The data do suggest the possibility that AMPT blocked the compensatory increase in biosynthesis of dopamine resulting subsequently in a disruption in development of morphine tolerance.…”
Section: Discussionmentioning
confidence: 95%
“…The timedependent effect rules out the possibility that AMPT acted proactively on processes directly associated with the test of analgesia. This is of importance because Major and Pleuvry (1971) demonstrated that AMPT potentiates the analgesic effects of morphine even though less extensive studies by Fenessy and Lee (1970) and Verri et al (1968) showed either no effect or an antagonistic effect upon morphine-induced analgesia. The data do suggest the possibility that AMPT blocked the compensatory increase in biosynthesis of dopamine resulting subsequently in a disruption in development of morphine tolerance.…”
Section: Discussionmentioning
confidence: 95%
“…These observations prompted an investigation of possible cholinergic and adrenergic involvement in the action of narcotic analgesic drugs rather than detailed studies of the mechanism by which these agents produce analgesia themselves. Major & Pleuvry (1971) were unable to find any differences in the mechanisms by which methylamphetamine and morphine had an antinociceptive effect in the mouse, using various pretreatments reported to induce changes in brain concentrations of 5-hydroxytryptamine, dopamine and noradrenaline.…”
Section: Introductionmentioning
confidence: 93%
“…For this purpose, the eVects of NAN-190 on methamphetamine-induced locomotor, anorectic, hyperthermic, and antinociceptive activities were investigated. The latter activity of methamphetamine is not well established as the former three activities, however, the amphetamines and many other sympathomimetics have long been known to produce analgesia (Ginawi et al, 1980;Leimdorfer and Metzner, 1949;Major and Pleuvry, 1971). Moreover sympathetic stimulation at times of excitement, anger or exercise can cause physiological analgesia in human.…”
Section: Introductionmentioning
confidence: 96%